2008
DOI: 10.1631/jzus.b0730019
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying biochemical variables of corn by hyperspectral reflectance at leaf scale

Abstract: Abstract:To further develop the methods to remotely sense the biochemical content of plant canopies, we report the results of an experiment to estimate the concentrations of three biochemical variables of corn, i.e., nitrogen (N), crude fat (EE) and crude fiber (CF) concentrations, by spectral reflectance and the first derivative reflectance at fresh leaf scale. The correlations between spectral reflectance and the first derivative transformation and three biochemical variables were analyzed, and a set of esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…In past efforts, remote estimation of canopy N content yielded the best results when applied to agricultural ecosystems of various types [35,[58][59][60]. This is perhaps to be expected.…”
Section: Discussionmentioning
confidence: 89%
“…In past efforts, remote estimation of canopy N content yielded the best results when applied to agricultural ecosystems of various types [35,[58][59][60]. This is perhaps to be expected.…”
Section: Discussionmentioning
confidence: 89%
“…Analyzing the mean determination coefficient values, scenarios considering reflectance data obtained a mean determination coefficient of 0.49 and scenarios considering FDR data obtained a mean determination coefficient of 0.50, Analyzing these two groups of data with the two-sample Student’s T-test it can be said that there are not significant differences between the mean values of these two groups with a p-value of 0.78. There are studies in the literature in which the use of the FDR presents advantages [ 29 , 44 , 45 ]. However, other studies concluded that the use of the FDR presents advantages only in specific situations [ 46 , 47 ], and there are also a few studies in the literature in which the use of the FDR does not present advantages at all [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the mean correlation values for all experiments, experiments that used reflectance data obtained a 67,059% of mean correlation and experiments that used FDR data obtained a 67,417%, which is not a significant difference. There are studies in the literature where the use of the FDR present advantages [28,42,43] but there are other studies in the literature where the use of the FDR present advantages only in specific situation [44,45]. Our study show neither advantages nor disadvantages using the reflectance data and the FDR data, which concurs with the literature review as it was said in the previous sentence.…”
Section: Methodology Evaluation Resultssupporting
confidence: 90%